2010
DOI: 10.1007/s11482-010-9129-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Life Satisfaction, and Self-Rated Health of Middle School Students

Abstract: Little research has examined the association between life satisfaction, selfrated health (SRH), and physical activity concurrently for middle school students. A convenience sample of 245 students in grades 7 and 8 was surveyed about physical activity, life satisfaction, and SRH using the U.S. Centers for Disease Control and Prevention (CDC) 2005 Middle School Youth Risk Behavior Survey. ANOVA analyses revealed significantly reduced life satisfaction for females who reported not engaging in vigorous physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 54 publications
9
40
0
2
Order By: Relevance
“…A possible selection effect may occur in that young people who feel healthy and good about their life are more prone to take up organized leisure activities such as football (Fletcher, Nickerson, & Wright, 2003). The findings are, however, in line with a previous study on the positive psychological experiences of participating in team sports (Zullig & White, 2011). In their study of a US convenience sample of 245 students in grades 7 and 8, significantly reduced life satisfaction was detected for adolescents who reported not playing on a sports team when compared to those who reported playing on a team.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A possible selection effect may occur in that young people who feel healthy and good about their life are more prone to take up organized leisure activities such as football (Fletcher, Nickerson, & Wright, 2003). The findings are, however, in line with a previous study on the positive psychological experiences of participating in team sports (Zullig & White, 2011). In their study of a US convenience sample of 245 students in grades 7 and 8, significantly reduced life satisfaction was detected for adolescents who reported not playing on a sports team when compared to those who reported playing on a team.…”
Section: Discussionsupporting
confidence: 86%
“…Findings reported by Hansen, Skorupski, and Arrington (2010) suggest that interdependent sports such as football, provide participants with greater opportunities to experience positive developmental experiences. Thus, based on previous studies suggesting positive outcomes from participating in football (Alvarez, et al, 2012;Balaguer, et al, 2012;Zullig & White, 2011), as well as growing evidence demonstrating the overall value of participation in organized activities for positive youth development (Farb & Matjasko, 2012;Hansen, et al, 2010;Leversen, Danielsen, Birkeland, & Samdal, 2012), it is likely that the higher scores on self-reported health and life satisfaction in the football sample are at least in part due to participants' football experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous studies reporting the critical role of positive personal attributes in promoting better physical and mental health Feldman and Sills [36]; Seligman & C sikszentmihalyi [3]; Wood & Tarrier [26]; Zullig and White [35], the present study empirically confirmed that BMI and the four positive constructs of psychological wellbeing significantly contributed to the students' physical and mental health.…”
Section: Discussionsupporting
confidence: 91%
“…In lieu of this mental health crisis, a growing number of research studies have shown that building psychological well-being is instrumental to reducing the symptoms of depression and anxiety Gilman et al [6]; Snyder and Shorey [20]; Snyder et al [19]; Zullig et al [35]; Zullig, et al [18]. In this study, the majority of Chinese university students self-reported that they felt somewhat and mostly grateful toward, hopeful for, happy about, and satisfied with their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Esta preocupación por la imagen corporal se destaca como uno de los principales motivos para practicar actividad físico deportiva junto con la satisfacción vital per se y la diversión vinculada con este tipo de ocio (Zullig, & White, 2011;Pedisic, Greblo, Phongsaban, Milton, & Bauman, 2015;Ahedo, & Macua, 2016;Fraguela, Varela, & Sanz, 2016).…”
Section: Introductionunclassified